PENGEMBANGAN PROFESI GURU SEBAGAI PENINGKATAN KINERJA GURU - P Praptiningsih (Institut Islam Mamba'ul 'Ulum Surakarta, 2020)
This article examines teachers and professional development in the world of education. The teacher is someone who plays an important role in the achievement of educational goals. To achieve this goal, professional teachers are very much needed, therefore the teacher's profession in each teacher must be developed. Professional teacher coach and development including the development of pedagogical competencies, personality competencies, social and professional competencies. Professional teacher development can be carried out at Teacher Professional Education Institutions because of that, becomes an institution that is specifically tasked with conducting teacher professional education and has the authority to become a teacher certification institution, despite teacher education programs and competency areas being taught the teacher is the responsibility of the Non-Teaching Study Program in the PT-LPTK (Teacher Training Institute).